Using self-cleavable ternary fusion pattern for efficient preparation of Bacteriorhodopsin. (January 2018) - Huang, Haihong; Yang, Bin; Ge, Baosheng; Lao, Jun; Zhou, Shitan; Huang, Fang
Graphical abstract: Highlights: High-level soluble expression of 7-transmembraned bO in E. coli has been achieved. The fusion protein can undergo controllable self-cleavage without exiguous enzymes. A simple and efficient method has been developed for purification of recombinant bO. Functional bR can be obtained by reconstituting the purified bO with retinal. Abstract: The study of membrane proteins has been notoriously hampered by its low expression level and difficulty in purification and crystallization. Therefore, development of efficient method for preparation of properly folded membrane proteins with milligram yield would be of critical importance. Here, we developed a simple and efficient strategy to obtain high purity of bacterio-opsion (bO), the apoprotein of bacteriorhodopsin (bR), in Escherichia coli ( E. coli ) using self-cleavable ternary fusion pattern. This method overexpresses bO as a ternary fusion protein, which can undergo controllable self-cleavage without addition of exiguous enzymes. After self-cleavage, there is no extra amino acid left on the native terminus of the bO. The final yield of bO can reach 270 mg/L with purity over 95%. BR can be obtained by reconstituting the purified bO with retinal in either n -Decyl-β-maltopyranoside (DDM) micelles or 1, 2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) vesicles. Our work provides a simple and efficient way for preparation of membrane proteins, and will be beneficial for their structural and functional studies.